1992
DOI: 10.2165/00003088-199223020-00005
|View full text |Cite
|
Sign up to set email alerts
|

P450 Enzymes

Abstract: Multiple hepatic P450 enzymes play an important role in the oxidative biotransformation of a vast number of structurally diverse drugs. As such, these enzymes are a major determinant of the pharmacokinetic behaviour of most therapeutic agents. There are several factors that influence P450 activity, either directly or at the level of enzyme regulation. Drug elimination is decreased and the incidence of drug interactions is increased when there is competition between 2 or more drugs for oxidation by the same P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(11 citation statements)
references
References 102 publications
0
9
0
2
Order By: Relevance
“…Effect of treatment with paracetamol on the serum ALT activities The estimation was done by using a photoanalyser (FT-2; AMS); serum ALT determination was carried out with a suitable kit (Autospan Diagnostic Reagent) containing the necessary reagents at a predetermined wavelength 340 nm where the rate of oxidation of NADH is measured kinetically by monitoring the decrease in absorbance at 340 nm (Murray, 1994).…”
Section: Biochemical Estimation Of Marker Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of treatment with paracetamol on the serum ALT activities The estimation was done by using a photoanalyser (FT-2; AMS); serum ALT determination was carried out with a suitable kit (Autospan Diagnostic Reagent) containing the necessary reagents at a predetermined wavelength 340 nm where the rate of oxidation of NADH is measured kinetically by monitoring the decrease in absorbance at 340 nm (Murray, 1994).…”
Section: Biochemical Estimation Of Marker Enzymesmentioning
confidence: 99%
“…The rate of oxidation of NADH is measured kinetically by monitoring the decrease in absorbance at 340 nm and is directly proportional to GOT activity in the sample (Murray, 1994).…”
Section: Effect Of Treatment With Paracetamol On the Serum Ast Activimentioning
confidence: 99%
“…Many studies have shown the effects of liver disease on CYP enzyme expression, and also the involvement of CYPs in the pathogenesis of disease [ 174 , 175 ]. For instance, the expression of CYP1A2, CYP2E1 and CYP3A was found to be decreased in cirrhotic and HCC patients, together with an alteration in the clearance of drugs metabolized by CYP3A4 [ 176 , 177 ]. Similarly, the expression of various CYP enzymes was altered in patients with NAFLD and ALD [ 178 , 179 ].…”
Section: Drug Metabolism Studies With Marmoset Esc-derived Hlcsmentioning
confidence: 99%
“…In many cases this information is incomplete or unknown, especially for older compounds. There are substantial genetic differences in the level of expression of certain enzymes, and age, gender and environmental factors may also influence enzyme activity (see below; for more detailed information on this extensive topic see Watkins, 1990;Cholerton er af., 1992;Murray, 1992;Brosen, 1993). For a given substrate, CYP450 enzymes may also be divided into two functional classes, based on whether they produce active or inactive metabolites.…”
Section: Important Cyp450 Enzymes In Manmentioning
confidence: 99%
“…ketoconazole, a CYP3A4 inhibitor, may slow the metabolism of certain benzodiazepines; fluoxetine may inhibit metabolism of some beta-blockers). A few of these interactions will be mentioned below, however a detailed review of the relationship between CYP450 enzymes and non-psychotropic drugs is beyond the scope of this article (for review see Watkins, 1990;Murray, 1992;Wrighton and Stevens, 1992). It is also important to note the shortcomings of some of the information in this area.…”
Section: Assessment Of the Role Of Individual Cyp45os In Drug Metabolismmentioning
confidence: 99%